2011
DOI: 10.1089/ten.tea.2010.0667
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Differentiation of Adult Bone Marrow-Derived Stem Cells to Liver Lineage in Aggregate Culture

Abstract: Hepatocyte-like cells derived from stem cells hold great potential for clinical and pharmaceutical applications, including high-throughput drug toxicity screening. We report a three-dimensional aggregate culture system for the directed differentiation of adult rat bone marrow-derived stem cells, rat multipotent adult progenitor cells, to hepatocyte-like cells. Compared to adherent monolayer cultures, differentiation in the aggregate culture system resulted in significantly higher expression level of liver-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
(65 reference statements)
3
10
0
Order By: Relevance
“…In the present study, a natural 3D scaffold from decellularized liver matrix was used to optimize the differentiation of MSC spheroids to functional hepatocytes. Our data demonstrated that the 3D biomatrix scaffold as well as spheroid culture promotes the induction of lineage-specific differentiation of MSCs into hepatocyte-like cells, which is consistent with the findings of other studies ( 15 17 , 20 , 21 ). Moreover, we suggest that the combination of cell-cell interactions and ECM plays a positive role in the differentiation of MSCs to hepatocyte-like cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, a natural 3D scaffold from decellularized liver matrix was used to optimize the differentiation of MSC spheroids to functional hepatocytes. Our data demonstrated that the 3D biomatrix scaffold as well as spheroid culture promotes the induction of lineage-specific differentiation of MSCs into hepatocyte-like cells, which is consistent with the findings of other studies ( 15 17 , 20 , 21 ). Moreover, we suggest that the combination of cell-cell interactions and ECM plays a positive role in the differentiation of MSCs to hepatocyte-like cells.…”
Section: Discussionsupporting
confidence: 93%
“…To prevent necrosis of the core caused by a deficiency of oxygen and nutrients, the diameter of the spheroid was controlled by the cell seeding density, culture time and the rocking speed. Previous 3D spheroid culture systems often involved a cell-accumulation technique in microwells with certain types of cells ( 15 , 16 ). However, these culture systems experienced difficulties in terms of producing sufficient numbers of MSC spheroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, enhanced differentiation of adult bone marrow-derived stem cells to liver lineage in a three-dimensional aggregate culture in comparison to adherent monolayer cultures has been demonstrated [88]. Taking into account that no special medium or substances facilitating hepatic differentiation were applied in our experimental set, we assume that a similar mechanism significantly contributed to the liver fetal cell-like differentiation of spheroid cells.…”
Section: Discussionsupporting
confidence: 64%
“…It is also suspected that the reprogrammed cells that underwent gene removal and FCM processes were susceptible to a decrease of viability and acquired hepatocyte function, whereas the cell-cell interactions in the spheroidal iHeps supported the maintenance of viability and promotion of differentiation into hepatocytes 39 40 41 . Thus, 3D culture environments including spheroids are expected to contribute to the maintenance and maturation of iHeps as reported for MSCs, iPSCs, and ESCs 42 43 44 , which could be an interesting avenue for future research.…”
Section: Discussionmentioning
confidence: 99%